2022
DOI: 10.1177/20406223221135011
|View full text |Cite
|
Sign up to set email alerts
|

Association between high-mobility group box 2 and subclinical hypertension-mediated organ damage in young adults

Abstract: Background: Hypertension-mediated organ damage (HMOD) is an emerging problem among young adults. The potential role of chronic immune-mediated inflammation in the pathogenesis of HMOD is increasingly being recognized. High-mobility group box 2 (HMGB2) is known for its role in the modulation of innate immunity and exerts signaling functions that affect various inflammatory diseases. However, the association between HMGB2 and HMOD in young adults remains unclear. Objectives: The aim of this study was to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…32 Thus, other circulating proteins originating from injured pulmonary vasculature may be more sensitive to early vascular pathology and useful in PH risk prediction. Consistent with the results of other studies, we previously found that serum HMGB2 was associated with in-stent restenosis and subclinical hypertension, 6,19 implying a role for serum HMGB2 in vascular pathological processes. The current study showed that HMGB2 expression was significantly increased in PAs, particularly in the smooth muscle layer in patients with PAH and in animal models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…32 Thus, other circulating proteins originating from injured pulmonary vasculature may be more sensitive to early vascular pathology and useful in PH risk prediction. Consistent with the results of other studies, we previously found that serum HMGB2 was associated with in-stent restenosis and subclinical hypertension, 6,19 implying a role for serum HMGB2 in vascular pathological processes. The current study showed that HMGB2 expression was significantly increased in PAs, particularly in the smooth muscle layer in patients with PAH and in animal models.…”
Section: Discussionsupporting
confidence: 92%
“…6 Moreover, high HMGB2 serum levels correlated with hypertension and end-organ damage in young adults. 19 The pathogenic features of PH are similar to hallmark characteristics of cancer, including excessive proliferation, apoptosis resistance, and metabolic change to glycolysis (Warburg effect). 20 Under the condition of chronic hypoxia and monocrotaline (MCT) treatment, HMGB1 levels are elevated in lung tissue and blood plasma and the increased HMGB1 level contributes to the development of PH in animal models.…”
mentioning
confidence: 99%
“…Additionally, as an immunomodulatory molecule, ASS1 modulates the immunological microenvironment and cytokine response via C-X-C motif chemokine ligand 8 (CXCL8) signaling [55]. HMGB2 is known for its proinflammatory role in mobilizing innate immunity and is involved in signaling pathways that are associated with various inflammatory disorders [56]. VIM is critical for nucleotide-binding oligomer-ization domain (NOD)-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome activation, and its loss leads to decreased levels of proinflammatory cytokines, subsequently protecting against harmful inflammation [57].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure accuracy, we aimed to have at least 10 outcome events per variable (EPV) 32 . Considering the documented prevalence of LVH in the general population, 12,13 particularly the incidence of 20.4% in our center, 33 we anticipated a 25% event rate for LVH in our research. To include 10 or fewer predictors in the final multivariable logistic regression model, we estimated that a sample size of 400 patients or more would be required.…”
Section: Methodsmentioning
confidence: 99%